Systematic review with meta‐analysis: dietary intake in adults with inflammatory bowel disease. Issue 6 (29th July 2021) - Lambert, Kelly; Pappas, Daniel; Miglioretto, Chiara; Javadpour, Arefeh; Reveley, Hannah; Frank, Laura; Grimm, Michael C.; Samocha‐Bonet, Dorit; Hold, Georgina L.
Summary: Background: Poor dietary intake is associated with the development of malnutrition, micronutrient deficiencies, anaemia and osteoporosis in individuals with inflammatory bowel disease. While trials are underway to manipulate the diet of people with IBD, there has been no comprehensive systematic review of the dietary intake of adults with IBD. Aims: To conduct a systematic evaluation and meta‐analysis of the dietary intake of adults with IBD, including macronutrients, micronutrients and food group data. Methods: CINAHL, Embase, Medline and Scopus were searched from 1 January 2000 to 25 September 2020 for cohort, case–control or cross‐sectional studies that reported usual dietary intake in adults. Data were pooled and reported as weighted mean intake for: all adults with IBD; Crohn's disease; ulcerative colitis; active disease; remission; males; females. A random‐effects meta‐analysis model compared intake with healthy individuals. Results: Forty studies were identified and 19 were included in the meta‐analysis. All subgroups of adults with IBD consumed inadequate energy (mean intake in adults with IBD 1980 ± 130 kcal), fibre (14 ± 4 g), folate (246 ± 33 mg) and calcium (529 ± 114 mg) per day. Intake of breads and cereals, legumes, fruit, vegetables and dairy were inadequate. Compared to healthy individuals, adults with IBD consume significantly less dietary fibre (SMD −0.59; 95% CI: −0.73, −0.46). Conclusions: This review provides improved clarity about the dietary intake of adults with IBD. Future attention is required to improve diet quality and increase understanding of factors influencing dietary intake in IBD. Abstract : 40 studies of 4070 adults with IBD and 11 504 healthy controls. ▪ Inadequate intake of energy, fibre, folate, calcium. ▪ Excessive sodium, meat and sugar consumption. ▪ Missing dietary data for many subgroups of the IBD population. ▪ Compared to healthy controls, adults with IBD consume less fibre (SMD: −0.59; 95% CI: −0.73, −0.46, P  < 0.00001).